2015
DOI: 10.1063/1.4926327
|View full text |Cite
|
Sign up to set email alerts
|

Reduced density-matrix functional theory: Correlation and spectroscopy

Abstract: In this work we explore the performance of approximations to electron correlation in reduced density-matrix functional theory (RDMFT) and of approximations to the observables calculated within this theory. Our analysis focuses on the calculation of total energies, occupation numbers, removal/addition energies, and spectral functions. We use the exactly solvable Hubbard molecule at 1/4 and 1/2 filling as test systems. This allows us to analyze the underlying physics and to elucidate the origin of the observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…This is in line with an analogous analysis on the Hubbard dimer. 38 It still remains to improve the band gap, which is overestimated in our method. This finding is consistent with the results on large Hubbard rings, which indicate that this overestimation is due to the use of δ (1) , and that the use of δ (2) might improve the spectrum and the band gap.…”
Section: B Realistic Systems: the Example Of Niomentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with an analogous analysis on the Hubbard dimer. 38 It still remains to improve the band gap, which is overestimated in our method. This finding is consistent with the results on large Hubbard rings, which indicate that this overestimation is due to the use of δ (1) , and that the use of δ (2) might improve the spectrum and the band gap.…”
Section: B Realistic Systems: the Example Of Niomentioning
confidence: 99%
“…We obtain good results (although the power functional does not recover the particle-hole symmetry) and, in particular, the band gap opens in the atomic limit, without breaking the symmetry. 38 We note that the gap strongly depends on the value of α: it has its maximum value for α = 0.5 while it disappears for α = 1 which corresponds to HF. For comparison we also report the results obtained using GW and the DER method: in the atomic limit these methods do not open any gap, unless the symmetry of the system is broken.…”
mentioning
confidence: 99%
“…j , which gives the exact groundstate energy for the half-filled Hubbard dimer [18,54]. We have however shown that the Müller functional predicts an unphysical infinite magnetic susceptibility for the half-filled Hubbard dimer [19].…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 99%
“…Several methods have been proposed to estimate photoemission spectra starting from Slater's transition state [70,103], local RDMFT [104,105] and approximations in terms of higher order RDMs [69]. Applications of these approaches to models systems [18,69] as well as real materials [69][70][71] showed mixed performances.…”
Section: Gaps and Spectral Informationmentioning
confidence: 99%
See 1 more Smart Citation